Conservation of Nickel Ion Single‐Active Site Character in a Bottom‐Up Constructed π‐Conjugated Molecular Network. (30th September 2022) - Baranowski, Daniel; Cojocariu, Iulia; Sala, Alessandro; Africh, Cristina; Comelli, Giovanni; Schio, Luca; Tormen, Massimo; Floreano, Luca; Feyer, Vitaliy; Schneider, Claus M.
Abstract: On‐surface chemistry holds the potential for ultimate miniaturization of functional devices. Porphyrins are promising building‐blocks in exploring advanced nanoarchitecture concepts. More stable molecular materials of practical interest with improved charge transfer properties can be achieved by covalently interconnecting molecular units. On‐surface synthesis allows to construct extended covalent nanostructures at interfaces not conventionally available. Here, we address the synthesis and properties of covalent molecular network composed of interconnected constituents derived from halogenated nickel tetraphenylporphyrin on Au(111). We report that the π‐extended two‐dimensional material exhibits dispersive electronic features. Concomitantly, the functional Ni cores retain the same single‐active site character of their single‐molecule counterparts. This opens new pathways when exploiting the high robustness of transition metal cores provided by bottom‐up constructed covalent nanomeshes. Abstract : The on‐surface synthesis of covalent nickel tetraphenylporphyrin network on Au(111) is studied by a multitechnique approach combining local microscopic insights with space‐averaging synchrotron radiation‐based methods. Even though the porphyrin nanomesh is not perfectly ordered extending the π‐system results in the appearance of energy‐dispersive electronic features while the Ni cores remain in the characteristic single‐molecule configuration.